Cervical strongyloidiasis in an immunocompetent patient: A clinical surprise - Sasmita Panda; Asaranti Kar; Upasana Das; Niranjan Rout (Wolters Kluwer Medknow Publications, 2015)
A 32-year-old lady came for a routine gynecological check up. Her cervical cytologic smear was reported as low grade squamous intraepithelial lesion. As a part of basic routine investigation, cervical punch biopsy was done. Astonishingly it revealed multiple rhabditiform larvae of Strongyloides stercoralis. These were curved thick with pointed end and a short buccal cavity. She did not have any history of immunosuppression including steroid therapy and was otherwise normal. Extensive review of the literature on parasites encountered in cervix yielded few case reports on strongyloides in cytologic smears, but failed to reveal any report till date on S. stercoralis found in histopathology section. Our case is probably the first in the world and the first reported from India to the best of our knowledge. We describe this case of strongyloidiasis of cervix with review of the literature on various parasites encountered in the cervix because of its rarity and also to keep this parasitic infestation as a differential diagnosis of cervical lesions.